2008
DOI: 10.1016/j.jmb.2007.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Remodeling of the Human Papillomavirus Type 11 Replication Origin into Discrete Nucleoprotein Particles and Looped Structures by the E2 Protein

Abstract: The human papillomavirus (HPV) origin (ori) of DNA replication shares a common theme with many DNA control elements in having multiple binding sites for one or more proteins spaced over several hundred base pairs. The HPV type-11 ori spans 103 bp and contains three palindromic binding sites (E2BS-2, E2BS-3, and E2BS-4) for the dimeric E2 origin binding protein. These sites are separated by 64 bp and 3 bp. E2BS-1 is located 288 bp upstream of E2BS-2 and is not required for efficient transient or cell-free repli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 38 publications
3
21
0
Order By: Relevance
“…A recent study has shown that HPV-11 E2 also forms loops with URR fragments containing E2BS, with a frequency similar to that in our results (36). As with BPV-1 and HPV-16, this study found that the full-length protein was necessary for loop formation, and the results suggested that the N-terminal TAD was responsible.…”
Section: Discussionsupporting
confidence: 89%
“…A recent study has shown that HPV-11 E2 also forms loops with URR fragments containing E2BS, with a frequency similar to that in our results (36). As with BPV-1 and HPV-16, this study found that the full-length protein was necessary for loop formation, and the results suggested that the N-terminal TAD was responsible.…”
Section: Discussionsupporting
confidence: 89%
“…Finally, both the E1 and E2 proteins are implicated in the higher order structure of the viral ori . While the role of the ori DNA structure in replication and maintenance is unknown, it is likely to be important for both replication and maintenance of the HPV genome (Abbate et al, 2004; Sim et al, 2008; Wilson et al, 2002). Importantly, the binding of polyamides is likely to alter the viral DNA conformation profoundly, including possibly at the ori , due to the well-known biophysical effects of polyamides on DNA such as widening the minor groove, shrinking the major groove, and stiffening the double helix (Dervan and Edelson, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The ori consists of a cluster of three E2 binding sites (BSs) flanking a series of overlapping E1 BSs. Three E2 dimers bind to the ori to form a toroidal ring, presumably partially denaturing the AT-rich E1 BSs in the negatively supercoiled DNA (Sim et al 2008). E2 interacts with E1 and recruits it to ori.…”
Section: The Functions Of E1 and E2 Proteins In Viral Dna Replicationmentioning
confidence: 99%